Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.devcel.2014.01.023
|View full text |Cite|
|
Sign up to set email alerts
|

Symmetry Breaking in Spore Germination Relies on an Interplay between Polar Cap Stability and Spore Wall Mechanics

Abstract: The morphogenesis of single cells depends on their ability to coordinate surface mechanics and polarity. During germination, spores of many species develop a polar tube that hatches out of a rigid outer spore wall (OSW) in a process termed outgrowth. However, how these awakening cells reorganize to stabilize this first growth axis remains unknown. Here, using quantitative experiments and modeling, we reveal the mechanisms underlying outgrowth in fission yeast. We find that, following an isotropic growth phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 62 publications
4
83
1
1
Order By: Relevance
“…Second, even with the slower vesicle delivery typical of yeasts, stochastic off-center vesicle delivery could yield displacement of the polarity site along the cortex (Figure 4) (Dyer et al 2013). Subsequent studies detected a mobile polarity site in mating S. cerevisiae cells (Dyer et al 2013, Hegemann et al 2015, McClure et al 2015) as well as germinating spores of S. pombe (Bonazzi et al 2014), suggesting that negative feedback by vesicle delivery may provide physiologically important functions.…”
Section: Mechanism Of Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, even with the slower vesicle delivery typical of yeasts, stochastic off-center vesicle delivery could yield displacement of the polarity site along the cortex (Figure 4) (Dyer et al 2013). Subsequent studies detected a mobile polarity site in mating S. cerevisiae cells (Dyer et al 2013, Hegemann et al 2015, McClure et al 2015) as well as germinating spores of S. pombe (Bonazzi et al 2014), suggesting that negative feedback by vesicle delivery may provide physiologically important functions.…”
Section: Mechanism Of Polarizationmentioning
confidence: 99%
“…A recent study on germinating spores of S. pombe suggested that the size of a Cdc42 cluster depends primarily on the micrometer-scale curvature of the membrane (Figure 7 d ) (Bonazzi et al 2015). In this system, Cdc42 clusters migrated around the cell before stabilizing to promote polarized growth (Bonazzi et al 2014). The size of the cluster changed significantly as it moved around the cell, with wider clusters observed at positions with flatter (lower-curvature) cell shape.…”
Section: Number and Size Of Polarity Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for negative feedbacks stems from observations of wave‐like and oscillatory dynamics, indicating reversal of polar cap growth by a negative control . This is perhaps best exemplified in S. pombe , where Cdc42 activity exhibits oscillations between the two cell poles during bipolar cell growth , around the cell cortex in mating cells exposed to low levels of pheromone , and around the spore periphery before outgrowth . Negative feedbacks have also been described in S. cerevisiae , with multiple zones of Cdc42 activity transiently seen to emerge and oscillate before stabilization of a single one in rsr1 Δ , and also in early G1 wild‐type cells , but another study did not observe transient multisite polarity emergence .…”
Section: The Actin Cytoskeleton‐based Vesicular Trafficking Reinforcementioning
confidence: 94%
“…Fungal spore germination is a complicated developmental process that starts with spores breaking dormancy in response to environmental stimuli and shedding their protective coat to then enter a so‐called isotropic growth phase during which they increase in volume mainly through the absorption of water from the environment. Once a certain volume is reached, a polarity axis is established from which a germ tube emerges, leading eventually to the formation of hyphae and mycelium (Osherov and May, ; Wendland, ; Fillinger et al ., ; van Leeuwen et al ., ; Bonazzi et al ., ).…”
Section: Introductionmentioning
confidence: 97%